Fabrication and mechanical properties of copper and silicon carbide-reinforced aluminum metal matrix composites processed by powder metallurgy - Endramawan, Tito; Kusmayadi, Adi; Suwandi, Dedi; Hudayef, Ayatullah (Politeknik Negeri Lhokseumawe, 2025)
Metal-matrix composites (MMCs) offer superior mechanical properties, making them ideal for advanced engineering applications. However, achieving optimal strength and hardness remains a challenge. This study investigated the role of copper (Cu) reinforcement in enhancing the mechanical performance of aluminum-silicon carbide (Al-SiC) composites fabricated via powder metallurgy. Composites were synthesized with 5 wt.% and 10 wt.% Cu and sintered at 500°C, 550°C, and 600°C. The results indicate that increasing Cu content significantly improved hardness and bending strength, with the 80%Al–10%Cu– 10%SiC composition exhibiting the highest hardness (96.86 kg/mm²) and bending strength (29.08 MPa) at 600°C representing a 37.86% and 74.03% increase, respectively, compared to the 5 wt.% Cu composites. Microstructural analysis confirmed uniform Cu and SiC dispersion, improved matrix bonding, and reduced porosity at elevated sintering temperatures. These findings highlight the potential of Cu-reinforced AlSiC composites for high-performance applications, particularly in wearresistant and structural components.